TEACHERS PERCEPTION OF THE IMPLEMENTATION OF MERDEKA CURRICULUM AT SMP IT FATHONA OKU BATURAJA AND SMP IT TUNAS CENDIKIA BATURAJA - Melin Dora Triskia; Henny Yulia; Nurul Afifah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2023)
The purpose of this research was to find out how teachers perception of Merdeka curriculum implementation at SMP IT Fathona OKU Baturaja and SMP IT Tunas Cendikia Baturaja. The design of this research is descriptive quantitative research. The technique sampling used in this research is a total sampling. The writer used a questionnaire to collect data. Based on the research results from the data analysis that has been carried out, it can be concluded that the teachers at SMP IT Fathona OKU Baturaja and SMP IT Tunas Cendikia Baturaja has a moderate perception of the implementation of the Merdeka Curriculum. The teachers understanding of the the implementation of the Merdeka Curriculum stage are good so that they can deepen its implementation, have a good understanding of merdeka belajar, understand there is a reduction in content that is beneficial for both teachers and students, the learning process that adapts to the character and needs of students. The existence of this positive perception is a supporter of successful implementation merdeka belajar curriculum at SMP IT Fathona OKU Baturaja and SMP IT Tunas Cendikia Baturaja. The results of questionaire showed that teachers at SMP IT Fathona OKU Baturaja and SMP IT Tunas Cendikia Baturaja has a positive perception and good appreciation of the implementation of the Merdeka Curriculum.